Endotoxin Acts Synergistically With Clostridioides difficile Toxin B to Increase Interleukin 1β Production: A Potential Role for the Intestinal Biome in Modifying the Severity of C. difficile Colitis. (29th March 2021) - Htwe, Pyae; Aung, Htay; Kywe, Bohm; Niang, Phyu T; Oo, Thar Sann; Monhandas, Sindhu; Kelly, Libusha; Goldman, David L
Abstract: Background: Inflammation is a crucial driver of host damage in patients with Clostridioides difficile colitis. We examined the potential for the intestinal microbiome to modify inflammation in patients with C. difficile colitis via the effects of gut-derived endotoxin on cytokine production. Methods: Endotoxin from Escherichia coli and Pseudomonas aeruginosa as well as stool-derived endotoxin were tested for their ability to enhance interleukin 1β (IL-1β) and tumor necrosis factor alpha (TNF-α) production by toxin B–stimulated peripheral blood mononuclear cells. Inflammasome and Toll-like receptor 4 (TLR4) blocking studies were done to discern the importance of these pathways, while metagenomic studies were done to characterize predominant organisms from stool samples. Results: Endotoxin significantly enhanced the ability of C. difficile toxin B to promote IL-1β production but not TNF-α. The magnitude of this effect varied by endotoxin type and was dependent on combined inflammasome and TLR4 activation. Stool-derived endotoxin exhibited a similar synergistic effect on IL-1β production with less synergy observed for stools that contained a high proportion of γ-proteobacteria. Conclusions: The ability of endotoxin to enhance IL-1β production highlights a manner by which the microbiome can modify inflammation and severity of C. difficile disease. This information may be useful in devising new therapies for severe C. difficile colitis. Abstract : Our study shows that endotoxin acts synergistically with Clostridioides difficile toxin B to increase IL-1β production. This effect varies among endotoxins from different gram-negative organisms and highlights a mechanism by which the gut microbiome can modify C. difficile disease severity.